Application of Emergency On Building Fire Using Ant Colony Optimization Method Based On Android - Khusaeri Andesa; Herwin Herwin (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Fire and Rescue Service is an agency to handles fire problems, i.e building fires. Fire and Rescue Service of Pekanbaru is an agency to handles fire problems in Pekanbaru where the service receives information about a fire incident quickly and responsively. Fire incidents can occur anywhere, in any location, both easy or difficult access, but the Firfighter Team must be prepared in every conditions. The problem is that not all fire incidents occur in easy access places by firefighters. The incidents sometimes occur in difficult places to reach and unknown location, firefighter have to use maps to find the location. It will be wasting time to find unknown location and took a long time to arrive. The solution of this problem is to build an android-based application that can be used as a fire incident report, which is connected in one application, so residents can report through an application automatically provides the coordinates of incident. The application of Ant Colony Optimization method in finding fire locations makes it easier to hasten in searching fire locations and can be used by the public in reporting fires to Fire and Rescue Service of Pekanbaru to be processed quickly.